Life Cycle Assessment of Local Rice Production at Limau Manis Padang, West Sumatra - Shabrina Nashya Aswin; Wiwit Juita Sari; Nurul Hathiqah; Rahma Dzulqa Dzulqa; Idil Saputra; Rilda Gumala; Aprialis Aprialis; Rahmatika Rahmatika; Novizar Nazir (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
Limau Manis is an area that is famous for producing rice, known as 'Sokan Limau Manis rice'. The development of sokan rice as a local product of Padang City can encourage increased rice production. The increase in production will affect the quality of the environment as a result of the entire series of sokan rice production activities. To find out the amount of emissions that can be generated from the Sokan Limau Manis rice production process, it is necessary to do an analysis using a Life Cycle Assessment (LCA). The LCA method can help identify and analyze the production cycle, the stages of the process, the flow of materials and materials as well as the energy that occurs during the rice production process in a comprehensive manner. Furthermore, the LCA method is able to provide an overview of the environmental impacts that can be generated from a series of rice production processes in which the implementation uses input raw materials that have the potential to damage the environment such as the use of chemical fertilizers. This research was conducted in Limau Manih Village, Pauh District, Padang City. The data used are primary data obtained from field observations and interviews with related parties. Primary data include the life cycle of rice, input and output of raw materials needed at each stage of the life cycle, as well as the use of tools and machinery at each stage of the life cycle. Secondary data includes the way the calculations are carried out, the value of emissions, and energy conversion. Sokan rice production system includes cultivation activities, rice refining until the final rice product is obtained requires input and energy consumption in the form of seeds, fertilizer, and diesel fuel as fuel. The development of Life Cycle Inventory (LCI) in the LCA analysis helps facilitate the process of data inventory in identifying the flow of raw materials in one production cycle of a product. The results of the analysis show that sokan rice produces emissions of 1.94 kg CO2eq / kg of rice produced with a total energy use value of 11,363.7 MJ / ton of rice. The largest CO2 emissions come from production and transportation activities, while the largest value of non-CO2 emissions comes from the stage of rice cultivation in the form of CH4 emissions. The value of CH4 emissions is influenced by the high use of fertilizers on the land. The improvement of the current system is more focused on reducing the consumption of synthetic fertilizers and increasing the use of organic materials and reuse of production waste to reduce the value of emissions on land and the environment